The thesan project: ionizing escape fractions of reionization-era galaxies. Issue 2 (19th January 2023) - Yeh, Jessica Y-C; Smith, Aaron; Kannan, Rahul; Garaldi, Enrico; Vogelsberger, Mark; Borrow, Josh; Pakmor, Rüdiger; Springel, Volker; Hernquist, Lars
Abstract: A fundamental requirement for reionizing the Universe is that a sufficient fraction of the ionizing photons emitted by galaxies successfully escapes into the intergalactic medium. However, due to the scarcity of high-redshift observational data, the sources driving reionization remain uncertain. In this work, we calculate the ionizing escape fractions ( f esc ) of reionization-era galaxies from the state-of-the-art thesan simulations, which combine an accurate radiation-hydrodynamic solver (arepo-rt ) with the well-tested IllustrisTNG galaxy formation model to self-consistently simulate both small-scale galaxy physics and large-scale reionization throughout a large patch of the universe (L_box = 95.5 cMpc ). This allows the formation of numerous massive haloes (M_halo 10^10 M_ ), which are often statistically underrepresented in previous studies but are believed to be important to achieving rapid reionization. We find that low-mass galaxies (M_stars 10^7 M_ ) are the main drivers of reionization above z ≳ 7, while high-mass galaxies (M_stars 10^8 M_ ) dominate the escaped ionizing photon budget at lower redshifts. We find a strong dependence of f esc on the effective star formation rate (SFR) surface density defined as the SFR per gas mass per escape area, i.e. Σ _SFR = SFR/M_gas/R_200^2 . The variation in halo escape fractions decreases for higher mass haloes, which can be understood from the more settled galactic structure, SFR stability, and fraction of sightlines within each halo significantly contributing to the escaped flux. Dust is capable of reducing the escape fractions of massive galaxies, but the impact on the global f esc depends on the dust model. Finally, active galactic nuclei are unimportant for reionization in thesan and their escape fractions are lower than stellar ones due to being located near the centres of galaxy gravitational potential wells.